NANOMATERIAL IN THE TREATMENT OF HEAVY METALS IN INDUSTRIAL WASTEWATER FROM THE NORTHERN REFINERIES COMPANY, IRAQ (Nativa, 2023)
In this study, a nanomaterial was synthesized from attapulgite clay to act as a new adsorption material. The synthesis of a compound (Attapulgite-NiCoFe2O4) was demonstrated within nanoscale measurements using X-ray Diffraction Measurements (XRD), Scanning Electron Microscopy (SEM), Surface Area Analysis, Vibrating Sample Magnetometer (VSM) and Transmission Electron Microscopy (TEM). Batch operations were carried out to study each of the effects of acidity, contact time, adsorbent dose, and ion concentration. The ideal values for the adsorption of lead were: pH (7), contact time (30) minutes, weight of the adsorption material (200 mg/L) and ion concentration (0.2 mg/L). The adsorption rate of lead was (88%).Keywords: attapulgite (NiCoFe2O4); copper (Cu); chromium (Cr); zinc (Zn); cadmium (Cd); lead (Pb). Nanomaterial no tratamento de metais pesados em águas residuais industriais da Companhia de Refinarias do Norte, Iraque RESUMO: Neste estudo, um nanomaterial foi sintetizado a partir da argila attapulgita para atuar como um novo material adsorvente. A síntese de um composto (Attapulgite-NiCoFe2O4) foi demonstrada em nanoescala por meio de medições de difração de raios X (XRD), microscopia eletrônica de varredura (SEM), análise de área superficial, magnetômetro de amostra vibrante (VSM) e microscopia eletrônica de transmissão (TEM). Operações em lote foram realizadas para estudar o efeito da acidez, tempo de contato, dose do adsorvente e concentração de íons. Os valores ideais para a adsorção de chumbo foram: pH (7), tempo de contato (30) minutos, peso do material de adsorção (200 mg/L) e concentração de íons (0,2 mg/L). A taxa de adsorção de chumbo foi de (88%).Palavras-chave: attapulgite (NiCoFe2O4), cobre (Cu); cromo (Cr); zinco (Zn); cadmium (Cd); prata (Pb).